The effect of regenerated MEG on hydrate inhibition performance over multiple regeneration cycles. (15th June 2018) - Alef, Khalid; Smith, Callum; Iglauer, Stefan; Gubner, Rolf; Barifcani, Ahmed
Graphical abstract: Highlights: Samples from a bench-scale MEG regeneration and reclamation pilot plant were evaluated for hydrate inhibition performance. Hydrate inhibition performance of MEG decreased as the regeneration cycles increased. Sample analysis revealed degradation products increased with cycle number. Thermal degradation of MEG can occur even if MEG is not exposed to its known degradation temperature range. An empirical model was developed to predict the decreasing effectiveness of MEG's hydrate inhibition over a specified number of regeneration cycles. Abstract: Mono-ethylene glycol (MEG) is a favorable gas hydrate inhibitor mainly due to its recoverability through MEG regeneration facilities, and thus reducing costs. However, it is not clear how the hydrate inhibition performance of MEG is affected by multiple regeneration cycles. In this study, MEG samples that were regenerated and reclaimed over multiple cycles using an innovative bench-scale MEG pilot plant which can simulate field-like MEG operations, were assessed on their hydrate inhibition performance. The cycled MEG samples were carefully analyzed in the laboratory for their composition, and each sample was tested in a high-pressure sapphire cell for methane hydrate inhibition performance. The study found a directly proportional relationship between the number of cycles and the shift in hydrate equilibrium phase boundary. A maximum equilibrium shift of 2.21 °C was recorded for a 20 wt% MEG/deionized water sample that had experienced 9 regeneration cycles compared to pure MEG. The analysis suggests that the shift in hydrate equilibrium phase boundary was due to thermal degradation of MEG within the regeneration and reclamation units due to the presence of acetic acid. The study found that even though the operation was below MEG degradation temperature range, repeated heating of MEG may have caused its degradation. Additionally, the phase equilibria are empirically modeled as a function of the number of cycles to aid MEG end-users. Application of the model to experimental results provided accurate outcomes, and had an average relative difference of 1.24% when determining equilibrium temperatures.